Improving Regional Financial Management through Administration of Regional Property and Financial Reporting on Regional Assets - Abdul Pattawe; Muhammad Ikbal Abdullah; Fikry Karim; Abdul Kahar; Muhammad Din; Femilia Zahra; Andi Chairil Furqan; Andi Ainil Mufidah Tanra; Dewa Made Adi Dharma (Research Horizon, 2022)
Local government financial management mechanisms have continued to undergo significant changes in recent years. This article seeks to reveal the process and analysis of academic activities to support the performance of the regional financial and asset management office as a form of assistance and understanding of regional financial and asset management as a form of knowledge. This activity was carried out at the Regional Financial and Asset Management Agency of Central Sulawesi Province, starting with the provision of a pre-test before socialization or presentation of material then interactive discussions between the service team and service participants. Participants were given a post-test afterwards. The ultimate goal of this activity is the transfer of knowledge possessed by the service team in the field of accounting, especially accounting for fixed assets in the field of government accounting, to managers of regional property and regional assets of Central Sulawesi Province. It is hoped that the government team can carry out better administration, bookkeeping and preparation of financial reports. Empirical analysis is also presented in this research.